2023
DOI: 10.1007/s40843-022-2311-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiperovskite nitride Cu3N nanosheets for efficient electrochemical oxidation of methanol to formate

Abstract: Perovskite oxides with flexible compositions and electronic structures have great potential for application in electrocatalytic water oxidation reactions. However, few studies have focused on the application of perovskite oxides in electrocatalytic oxidation reactions of organic molecules, probably due to the absence of active species because of the poor conductivity and high energy barrier of the surface reconstruction. Herein, we report Cu 3 N nanosheets with a typical antiperovskite structure as electrocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…42 Additionally, the N 1s and O 1s XPS spectra of the two prepared samples are also shown in Figure S3. 43 It also can be seen that the N 1s and O 1s XPS spectra no obvious changes after loading Pt in Pt/WN and Pt/ W 18 O 49 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…42 Additionally, the N 1s and O 1s XPS spectra of the two prepared samples are also shown in Figure S3. 43 It also can be seen that the N 1s and O 1s XPS spectra no obvious changes after loading Pt in Pt/WN and Pt/ W 18 O 49 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…For the W 4f spectrum in Pt/WN (Figure S2a), the two peaks at 32.4 and 34.3 eV belong to the W–N bond, while 35.3 and 37.5 eV are classified as the W–O bond due to the inevitable surface oxidation by exposure to air. W 4f in Pt/W 18 O 49 (Figure S2b) has only two peaks of the W–O bond at 35.8 and 38 eV, which are ascribed to W 4f 7/2 and W 4f 5/2 , respectively . Additionally, the N 1s and O 1s XPS spectra of the two prepared samples are also shown in Figure S3 . It also can be seen that the N 1s and O 1s XPS spectra no obvious changes after loading Pt in Pt/WN and Pt/W 18 O 49 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Transition-metal nitrides (TMNs), an important class of inorganic materials featuring the interstitial nitrogen atoms within the metal matrix and the noble metal-like electronic structures, have been proven to be efficient in electro-, photo-, and thermal catalyses and are drawing broad interest in the catalysis community. For example, Xu et al found that selenium-doped Co 4 N is an efficient electrocatalyst for hydrogen evolution reactions due to its modulated surface electronic structures . Yang et al employed tungsten nitride as a metallic photocatalyst for overall water splitting under red-light irradiation, confirming the important role of the metallic properties in exhibiting photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, Xu's group revealed that the in situ -formed Cu 2+ species on the surface of Cu 3 N could act as active sites for methanol electro-oxidation, which is the key active phase for the formation of formate. 18 Notably, owing to the relatively low structural stability of the transition-metal-based catalysts, the operational stability for long-term EMU catalysis is still not satisfactory to date, and needs to be strengthened via preferential microstructural design. Previous work reported that the nitrogen-doped carbon (Co–N–C) derived from the pyrolysis of a Co-based zeolitic imidazolate framework (ZIF-67) could not only effectively protect the active phase against structural collapse and degradation of activity, but also promote the electrochemical pre-oxidation process to accelerate the generation of more active sites for electro-oxidation reactions, benefitting from the enhanced conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a series of transition-metal-based catalyst compounds have been explored for EMU, and current studies indicate that high-valence transition metal ions could serve as catalytically active sites for methanol-to-formate conversion. 5,15,[17][18][19][20][21][22] Hence, enriching local high-valence species or promoting the in situ generation of such active sites via an electrochemical pre-oxidation process could effectively improve EMU behavior. For example, Peng and colleagues fabricated an Fe 2 O 3 /NiO heterojunction catalyst, which could lead to the stabilization of high-valence Ni 3+ ions as active sites for EMU and further realize enhanced catalytic activity via beneficial Ni-O-Fe interfaces.…”
Section: Introductionmentioning
confidence: 99%